2017
DOI: 10.1590/1806-9282.63.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Alert for bone alterations and low serum concentrations of vitamin D in patients with intestinal inflammatory disease

Abstract: Background: Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are characterized by chronic inflammation of the intestine that can reduce the absorption of nutrients such as vitamin D and calcium. Objective: To investigate bone alterations and serum levels of vitamin D in patients with IBD. Method: This was a cross-sectional study based on a review of medical records of patients from a private office in Curitiba, PR, Brazil. Serum levels of vitamin D and bone densito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
1
8
0
4
Order By: Relevance
“…The level of 25(OH)D was within the lower limit of the normal range among the studied children with CD. In other studies, similar results are observed and in some cases serum levels are even lower [27,36,37]. The morphological parameters of the blood were mostly normal, with the exception of low hemoglobin and hematocrit, and elevated monocyte counts in girls.…”
Section: Discussionsupporting
confidence: 82%
“…The level of 25(OH)D was within the lower limit of the normal range among the studied children with CD. In other studies, similar results are observed and in some cases serum levels are even lower [27,36,37]. The morphological parameters of the blood were mostly normal, with the exception of low hemoglobin and hematocrit, and elevated monocyte counts in girls.…”
Section: Discussionsupporting
confidence: 82%
“…This could underestimate the true weight that the latter may have as predictors of vitamin D deficiency. On the other hand, this is one of the few studies on the subject performed in a South American setting, apart from a recently published study by Kotze et al (18) .…”
Section: Discussionmentioning
confidence: 93%
“…Osteoporosis is typically a multifactorial disease. The pathogenic mechanisms that might contribute to low BMD in IBD patients include advancing age, low BMI, smoking, alcohol abuse, immobilization or inactive lifestyle, the activation of inflammatory cytokines, hypogonadism, malnutrition, intestinal malabsorption of calcium and vitamin D, the use of corticosteroids, and genetic susceptibility [4,33].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that patients with Inflammatory Bowel Disease (IBD) are at increased risk for osteopenia and osteoporosis. Osteopenia and osteoporosis are common extraintestinal complications in IBD that increase the Several studies have demonstrated a decrease in Bone Mineral Density (BMD) in patients with Crohn's Disease (CD), and to a less extent in Ulcerative Colitis (UC) [4]. The higher prevalence of bone disease in CD patients is thought to be related to ileal and small intestine involvement of diseasecausing vitamin D and calcium malabsorption, estrogen deficiency and malnutrition [1,5].…”
Section: Introductionmentioning
confidence: 99%